IMPROVING POST PARTUM MOTHER'S SKILLS IN PERFORMING OXYTOCIN MASSAGE TO PREVENT LACTATION PROBLEMS - Rahmi, Rifa; Ruspita, Rika; Susanti, Komaria (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Improving human quality must start as early as possible, namely since infancy, one of the factors that plays an important role in improving human quality is the provision of breast milk. Breast milk is very good food for babies, where based on the low percentage of exclusive breastfeeding, it has an impact on the nutritional status of infants. The success of exclusive breastfeeding in Indonesia was recorded at 66.1%. Riau Province recorded 78% success of exclusive breastfeeding. This service is carried out in order to improve the skills of postpartum mothers in carrying out breast massage to prevent lactation problems. Community service activities are supported by counseling methods, questions and answers, and discussions and demonstrations of lactation massage. The result was that postpartum mothers were enthusiastic about participating in community service activities which were carried out with demonstrations and understood the steps or ways to do lactation massage so that it could be concluded that this community service activity ran smoothly.